1999
DOI: 10.1038/sj.bjc.6690495
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of the p16INK4a gene in plasma DNA of breast cancer patients

Abstract: Summary Hypermethylation of exon 1 of p16 INK4a was examined in tumour and plasma DNA of a series of breast cancer patients. De novo methylation was observed in the tumours of eight patients (23%), and in plasma DNA in five (14%) of these eight patients. Our data show that de novo methylation of exon 1 of p16 INK4a can be demonstrated in plasma DNA of breast cancer patients, a fact that provides additional evidence of the tumour-related origin of free plasma DNA in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 24 publications
2
55
0
2
Order By: Relevance
“…In addition to analysis of DNA extracted from cancer samples, free DNA in the plasma or serum is known to be present in cancer patients (Shapiro et al, 1983;Stroun et al, 1989). Taking advantage of the high sensitivity of MSP, aberrant methylation in the plasma or serum DNA is now being used in a variety of cancer diagnoses (Esteller et al, 1999;Silva et al, 1999;Kawakami et al, 2000). From the high incidence of 3-OST-2 methylation in the primary cancer samples, detection of the aberrant methylation in plasma or serum DNA is expected to be useful as a tumor marker.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to analysis of DNA extracted from cancer samples, free DNA in the plasma or serum is known to be present in cancer patients (Shapiro et al, 1983;Stroun et al, 1989). Taking advantage of the high sensitivity of MSP, aberrant methylation in the plasma or serum DNA is now being used in a variety of cancer diagnoses (Esteller et al, 1999;Silva et al, 1999;Kawakami et al, 2000). From the high incidence of 3-OST-2 methylation in the primary cancer samples, detection of the aberrant methylation in plasma or serum DNA is expected to be useful as a tumor marker.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been proposed that analyses of free plasma DNA could be a useful tool for prognosis or the early diagnosis to detect subclinical disease recurrence [4]. Since the introduction of PCR-based techniques in the late 1980s, a large number of tumorspecific alterations have been identified in free plasma DNA, such as K-ras mutations in patients with colorectal cancer [5], microsatellite alterations in patients with smallcell lung cancer [6], head and neck cancer [7], clear cell renal carcinoma [8] and melanoma [9], and finally aberrant promotor hypermethylation of tumor suppressor genes in patients with non-small-cell lung cancer [10], liver [11], and breast cancer [12]. Whereas the majority of these studies examined patients with solid tumors, it has also been suggested that free plasma DNA can be used for the detection of molecular abnormalities in hematological malignancies [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of circulating cell-free DNA in serum or plasma (15,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)) presents a new opportunity for identifying MGMT promoter methylation in tumor cells. There have been limited reports on the concordance between serum, plasma, or sputum and tumor methylation biomarkers in patients, such as APC promoter methylation in lung cancer (29); hMLH1 promoter methylation in CRC (23); p16 methylation in NSCLC, H&N, esophageal, breast, and hepatocellular cancers (15,24,28,30,32); and MGMT methylation in lung cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…There have been limited reports on the concordance between serum, plasma, or sputum and tumor methylation biomarkers in patients, such as APC promoter methylation in lung cancer (29); hMLH1 promoter methylation in CRC (23); p16 methylation in NSCLC, H&N, esophageal, breast, and hepatocellular cancers (15,24,28,30,32); and MGMT methylation in lung cancer (44). Although these reports used similar MSP analysis, the concordance between assays of tumor and surrogate tissue varied across different cancer types and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation